Temperament and social competence in preschool children from San Juan de Lurigancho: a preliminary study - Bárrig Jó, Patricia Susana (2017)
The goal of this study was to determine the relationship between temperament, social competence, and behavioral problems in preschool-age children. The study is based on a sample of 66 children, 40 males and 26 females, between 2 and 6 years old (M = 3.92, SD = 1.01), and their mothers. Temperament was assessed using the Children’s Behavior Questionnaire, Short Version (CBQ; Putnam & Rothbart, 2006), which provides data on the dimensions of Surgency, Negative Affect, and Effortful Control. We used the Social Competence and Behavior Evaluation Scale (SCBE-30, LaFreniere & Dumas, 1996) to assess Social Competence as well as problems of Anxiety and Aggressive behavior in children. First, boys showed lower scores in both Negative Affectivity and Effortful Control than girls. The study’s main analysis identified a significant negative association between Surgency and Anxiety. In addition, the three dimensions of temperament were associated with aggression-behavioral problems: Surgency and Negative Affectivity in a positive direction, whereas Effortful Control was associated negatively. Finally, Effortful Control showed a moderate and positive correlation with social competence. These results are consistent with contemporary theoretical and empirical evidence on the topic. However, future studies should consider larger samples to know the scope of temperament and social competence in preschool-age children. DOI: https://doi.org/10.24265/liberabit.2017.v23n1.05